Using Large Institutional or National Databases to Evaluate Prostate Cancer Outcomes and Patterns of Care: Possibilities and Limitations - Daniel Su; Thomas L. Jang (The Scientific World Journal)
Prostate cancer is the most common non–skin-related cancer in men. With advances in technology, the care and treatment for men with this disease continues to become more complex. Large databases offer researchers a unique opportunity to conduct prostate cancer research in various areas, and provide important information that helps patients and providers determine prognosis after treatment. Furthermore, the studies using these databases may provide information on how side effects from various treatments can affect one's quality of life. Finally, information from these datasets can help to identify factors that determine why patients receive the treatments they do. Despite this, these databases are not without limitations. In this review, we discuss various available, national, multicenter, and institutional databases in the context of prostate cancer research, citing numerous important studies that have impacted on our understanding of prostate cancer outcomes.